Twin peaks diversity with sacubitril/valsartan treatment responses in cardiomyopathic heart failure patients of non-ischemic compared to ischemic etiologies. (25th November 2020) - Chang, H.Y; Chiou, W.R; Lin, P.L; Hsu, C.Y; Liao, C.T; Lee, Y.H; Lin, C.C; Tsao, T.P; Yin, W.H
Abstract: Background: Ischemic cardiomyopathy (ICM) has been associated with increased mortality when compared with non-ischemic cardiomyopathy (NICM) from several heart failure (HF) cohorts. Instead, PARADIGM study demonstrated similar event rates of cardiovascular (CV) death, all-cause mortality and HF readmissions between ICM and NICM patients. Although the beneficiary effect of sacubitril/valsartan (SAC/VAL) compared to enalapril on these endpoints was consistent across etiologic categories, PARADIGM study did not analyze the effect of ventricular remodeling of SAC/VAL on patients with different HF etiologies, which may significantly affect treatment outcomes. Purpose: We aim to compare alterations of left ventricular ejection fraction (LVEF) following SAC/VAL treatment and its association with clinical outcomes in patients with different HF etiologies. Methods: Treatment with angiotensin receptor neprilysin inhibitor for Taiwan heart failure patients (TAROT-HF) study is a multicenter study which enrolled 1552 patients with LVEF <40%, whom had been on SAC/VAL treatment from 9 hospitals between 2017 and 2018. After excluding patients without having follow-up echocardiographic studies, patients were grouped by HF etiologies and by LVEF changes following treatment for 8-month period. LVEF improvement ≥15% was defined as "significant improvement", 5–15% as "marginal improvement", and <5% or worse as "lack of improvement". The primary endpoint was a composite of CV death or a first hospitalization for HF. Mean follow-up period was 726 days. Results: A total of 1230 patients were analyzed. Patients with ICM were significantly older, more male, and prone to have associated hypertension and diabetes. On the other hand, patients with NICM had lower LVEF and higher likelihood of atrial fibrillation. LVEF increase was significantly greater in patients with NICM compared to those with ICM (11.2±12.4% vs. 6.9±9.8, p<0.001). The effect of ventricular remodeling of SAC/VAL on patients with NICM showed twin peaks diversity (Significant improvement 37.1%, lack of improvement 42.3%), whereas in patients with ICM the proportions of significant, marginal and lack of improvement groups were 19.4%, 28.2% and 52.4%, respectively. The primary endpoint showed twin peaks diversity also in patients with NICM in line with LVEF changes: adjusted HR for patients with NICM and significant improvement was 0.41 (95% CI 0.29–0.57, p<0.001), for patients with NICM and lack of improvement was 1.54 (95% CI 1.22–1.94, p<0.001). Analyses for CV death, all-cause mortality, and HF readmission demonstrated consistent results. Conclusion: Patients with NICM had higher degree of LVEF improvement than those with ICM following SAC/VAL treatment, and significant improvement of LVEF in NICM patients may indicate favorable outcome. NICM patients without response to SAC/VAL treatment should serve as an indicator for poor clinical outcome and warranted meticulous HF management. Funding Acknowledgement: Type of funding source: Private hospital(s). Main funding source(s): Cheng Hsin General Hospital